(untitled) (Historia, 2021)
Bird's-eye view of an Afrikaner history over 350 years The formation of an Afrikaner people can be best understood as the outcome of certain forces: a relative balance between the sexes in the white population after 1725; the role of the church and the relatively strong position of white women. the unfolding of South African history can be understood in terms of C.W. de Kiewiet's dictum of South Africa as a country of low grade land, low grade gold and low grade people. the first refers to the fact that only a small part of South Africa is arable. It led to migrants farmers dispersing over a large area and becoming dependent on black and brown labour. Low grade gold sucked large numbers of workers to the Witwatersrand and reinforced the trend towards heavy use of migrant black labourers. By low grade people De Kiewiet meant the lack of qualifications of a large part of the labour force, including Afrikaner workers. This was the background against which the policies of segregation and apartheid were introduced.